Investigating Children's Programming Skills Through Play with Robots (KIBO) - Lee, Joohi; Yunus, Sham’ah; Lee, Joo Ok (Early childhood education journal, 2025)
Robotics has emerged as a popular interdisciplinary pedagogical approach in the field of education to teach children STEM concepts. By providing playful learning experiences, the use of robots engages children in an active learning process, making it an effective tool to promote their targeted knowledge, skills, and disposition towards STEM, including programming and coding skills. This study aimed to investigate the impact of using a programmable robot (KIBO) as a station activity and how it impacts pre-kindergarteners' programming skills after 2 weeks of play. Fourteen children aged 3–4 participated in the study during the summer, with the robot station activity lasting for 40 min each day. Results indicated a significant improvement in all areas of programming skills, including copying programming (n = 13), programming (n = 13), programming with a conditional statement (n = 7), and decoding (n = 10), after playing with the robot. The findings suggest that incorporating programmable robots as station activities can be a valuable addition to pre-kindergarten curriculums to promote basic programming skills in young children, which can serve as a foundation for future STEM learning. Further research is needed to determine the long-term effects of using robots as a teaching tool for young children.